Contractor Capacity and Waste Generation: An Empirical Investigation - Seneviratne, Krisanthi; Rameezdeen, Raufdeen; Amaratunga, Dilanthi (Penerbit Universiti Sains Malaysia, 2015)
: This paper aims to test the hypothesis that an inverse relationship exists between the capacity of a contractor and the amount of waste generated in a construction site. In Sri Lanka, contractors are graded by an independent government agency and this study uses 15 projects undertaken by grade M1 to M5 contractors. M1 contractors constitute the highest grade and they have higher technical, financial and managerial capabilities. These projects are examined to determine cement wastages and link them to these respective grades to clarify their relationship. The major finding is that upper grade contractors, who are more capable, generate less waste compared to their lower grade counterparts. This suggests that contractor capacity not only has desirable outcomes for better time, cost and quality objectives but also benefits the environmental objectives of their clients. While the present grading system in Sri Lanka does not consider waste management, it is suggested that the waste management practices of contractors could vary immensely from the M1 grade to the lower grades. Consequently, future revisions in the grading system should seriously consider incorporating waste management practices to provide an incentive to contractors who appropriately manage their waste. In theory, this will encourage efficient waste reduction practices in construction sites.